LEGAL CONSEQUENCES FOR ADOLESCENT NARCOTICS ABUSERS BASED ON THE LAW NUMBER 35 YEAR 2009 - ASIS, ABD; SAMPURNO S, SLAMET; ILYAS, AMIR; INDRAWATI, DARA; KADARUDIN; DWI PRATIWI, SITI ISTI; GHITA SYAHFITRI, ERVINADIA (Sekolah Tinggi Ilmu Hukum Awang Long, 2020)
This paper aims to analyze the legal paradigm of Law of the Republic of Indonesia Number 35 Year 2009 concerning Narcotics and legal arrangements for adolescent narcotics abusers. This type of research is normative using a statutory approach. The data used is secondary data obtained through library research. All data collected were then analyzed qualitatively. The results showed that the legal paradigm of the Law of the Republic of Indonesia Number 35 Year 2009 concerning Narcotics is to prioritize community participation in efforts to prevent and eradicate abuse of Narcotics and Narcotics Precursors and to create a deterrent effect on perpetrators of abuse and illicit trafficking of Narcotics and Narcotics Precursors. imposition of criminal sanctions, whether in the form of a special minimum sentence, imprisonment of 20 years, up to death penalty. The legal arrangement for juvenile narcotics abusers refers to Article 1 point 3 of the Law of the Republic of Indonesia Number 11 Year 2012 concerning the Juvenile Criminal Justice System. If the narcotics user is a teenager who has not reached the age of 18 years, the criminal sentence that can be imposed on the child is a maximum of 1/2 of the maximum imprisonment for adults as stipulated in the Law of the Republic of Indonesia Number 35 Year 2009 concerning Narcotics.